2013
DOI: 10.1016/j.immuni.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

RORγt+ Innate Lymphoid Cells Acquire a Proinflammatory Program upon Engagement of the Activating Receptor NKp44

Abstract: RORγt⁺ innate lymphoid cells (ILCs) are crucial players of innate immune responses and represent a major source of interleukin-22 (IL-22), which has an important role in mucosal homeostasis. The signals required by RORγt⁺ ILCs to express IL-22 and other cytokines have been elucidated only partially. Here we showed that RORγt⁺ ILCs can directly sense the environment by the engagement of the activating receptor NKp44. NKp44 triggering in RORγt⁺ ILCs selectively activated a coordinated proinflammatory program, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
179
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(193 citation statements)
references
References 32 publications
(60 reference statements)
14
179
0
Order By: Relevance
“…Some evidences, however, indicate that the engagement of NKp44 in ILC3 may induce TNF-α production and synergize with IL-1, IL-7, and IL-23 to induce secretion of IL-22 (a cytokine typically produced by ILC3s). 62 In a recent study, the transcriptome analysis of NKp44-stimulated ILCs revealed a “genome wide regulating effect”. 62 This finding is in line with our present proteomic study showing that NK cell stimulation both via mAb-mediated NKp44 cross-linking and by plastic-bound NID1 could induce significant changes in a relevant number of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidences, however, indicate that the engagement of NKp44 in ILC3 may induce TNF-α production and synergize with IL-1, IL-7, and IL-23 to induce secretion of IL-22 (a cytokine typically produced by ILC3s). 62 In a recent study, the transcriptome analysis of NKp44-stimulated ILCs revealed a “genome wide regulating effect”. 62 This finding is in line with our present proteomic study showing that NK cell stimulation both via mAb-mediated NKp44 cross-linking and by plastic-bound NID1 could induce significant changes in a relevant number of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…62 In a recent study, the transcriptome analysis of NKp44-stimulated ILCs revealed a “genome wide regulating effect”. 62 This finding is in line with our present proteomic study showing that NK cell stimulation both via mAb-mediated NKp44 cross-linking and by plastic-bound NID1 could induce significant changes in a relevant number of proteins. Consistent with the multiple ligand specificities of NKp44 and its ability to mediate different functional responses, NKp44 cross-linking and NID1-induced stimulation resulted in protein changes that were only partially overlapping.…”
Section: Discussionmentioning
confidence: 99%
“…NKp46 + ILC3 are characterized by subset‐restricted expression of multiple genes required for their development and maturation, such as Il12rb2 , Tbx21 and Notch1 ,51, 61 and are defined by expression of eponymous NK cell‐associated receptors. Recent evidence suggests that NKp46 expression may act as a novel pattern recognition molecule to facilitate responses to fungal pathogens,62 whereas engagement of NKp44 on human ILC3 results in pro‐inflammatory cytokine production 63. Although NCR + ILC3 are largely thought to be non‐cytotoxic cells, NKp46 + ILC3 express Gzmc – which encodes a murine granzyme molecule known to induce cell death 60, 64.…”
Section: Ilc3 Plasticity and Heterogeneitymentioning
confidence: 99%
“…NCR + ILC3 are cellular sources of the tissue protective cytokine IL‐22 4. Additionally, engagement of NKp44 triggers TNF release providing a pro‐inflammatory function for NCR + ILC3 26. The NCR − ILC3 secrete little IL‐22 but do produce IL‐17, similarly to the LTi‐like ILC3 in the mouse 25.…”
Section: Ilc Subsetsmentioning
confidence: 99%